Premisas de diseño para el buen desempeño térmico en la construcción con contenedores marítimos : caso estudio en el pacífico norte de Costa Rica - Ortiz Cabezas, Alejandro (Arquitectura, Arte y Diseño, 2018)
The construction of living spaces from shipping containers is a common practice now a day. They offer an economic, versatile and quick way of habilitating spaces for a determined activity such as commercial, industrial, residential, etc. In Costa Rica it is qualified as a low cost construction typology due to the fact that it is a prefabricated element however the market practices can elevate its cost comparable to a traditional concrete block typology. On the other hand due to the shipping containers material, certain bioclimatic strategies can be inferred in order to habilitate it correctly without a clear reference to the effect of these in its thermal performance. Its due to these lack of quantitative information that this thermal performance investigation is made on a 20 foot shipping container to see the effect of applying different passive climatic strategies in a warm dry climate. With the use of software simulation the results are generated to asses and determine design premises with which to achieve a performance as close to the comfort zone established. With this the improvement in thermal performance can be quantified depending on the passive strategy applied